Science knowledge and attitudes of lifelong learners in an astronomy massive open online course. Issue 2 (3rd April 2021) - Impey, Chris; Formanek, Martin; Buxner, Sanlyn; Wenger, Matthew
ABSTRACT: The basic science knowledge and attitudes toward science have been compared for (1) adult free-choice learners in an astronomy online course or MOOC, (2) undergraduate non-science majors, and (3) professional scientists from graduate student to professor level. The adult MOOC learners have a higher level of science knowledge than the college students, as measured using an NSF instrument, and they display fewer science misconceptions and a deeper view of how science works. They also have more positive attitudes toward science and technology and lower levels of belief in pseudoscience and superstition. Compared to professional scientists at any level, both student groups showed a more limited and shallow view of how science works. These results inform efforts to help free choice learners engage in science so that they can meaningfully participate in the many societal and policy debates that hinge on science.